Aforização no discurso de autoajuda - Brunelli, Anna Flora [UNESP] (My University, 2011)
In this paper, based on Maingueneau’s (2006, 2010) thoughts on aphorisation and on the differences between aphorising and textual enunciation, we analyze some detached utterances from the self-help discourse, by highlighting some of their meaning effects and their role in such discourse. The analysis shows that the aphorising detachments support the self-help discourse enunciator in the process of guiding the interlocutors. Such aphorizing detachments allow the enunciator to give order as if he or she were enunciating the truth, which attenuates the enunciator’s authoritative character, who is supposed to give order explicitly. Moreover, such utterances activate the play between “to say and not to say,” by simulating that the self-help discourse is based on an undeniable truth, which reinforces its persuasive power.

Neste trabalho, considerando as reflexões de Maingueneau (2006, 2010) sobre a aforização e as diferenças entre a enunciação aforizante e a textualizante, analisamos alguns enunciados destacados do discurso de autoajuda, procurando evidenciar alguns dos seus efeitos de sentido e o papel que desempenham nesse discurso. A análise revela que os destaques aforizantes auxiliam o sujeito enunciador do discurso de autoajuda no trabalho de orientação de seus interlocutores, pois lhe permitem dar uma ordem, como se estivesse enunciando uma verdade, o que atenua o seu caráter de sujeito autoritário, próprio de quem dá ordens de modo explícito. Além disso, esses enunciados ativam o jogo do “dizer e não dizer”, simulando que o discurso de autoajuda está apoiado numa verdade incontestável, o que lhe reforça o poder persuasivo.
Keywords: aforização; discurso autoajuda; Aphorisation; Detached Utterances; Discourse; Self-Help